CONFESSIONS OF A UTOPOPHOBE. Issue 1 (7th December 2016) - Huemer, Michael
Abstract: Ideal theorists in political philosophy seek to describe a perfect political society, and to evaluate political principles by reference to their consequences in a world where everyone complies with the principles. I argue that ideal theory is not needed to set goals for practical inquiries, nor to define justice, nor to enable rankings of injustices. Nor is it useful to theorize about very different kinds of society that might occur in the far future. Ideal theory tempts us to make each of three kinds of error: it tempts us to propose norms that no specific agent can act on, to posit crazy exaggerations of moral virtues, and to place too much trust in abstract philosophical reasoning. A better approach to normative questions is to rely on analogical arguments starting from uncontroversial intuitions about concrete scenarios.